Negotiating trade : developing countries in the WTO and NAFTA - Odell, John S., 1945- (Cambridge University Press, 2006)
Negotiations between governments shape the world economy and thus the lives of people everywhere. This innovative book reports the inside story about how developing countries negotiate in the WTO and regional talks, which strategies they use, coalition formation, and how they learn and influence other countries' beliefs.